2017
DOI: 10.1111/jbg.12288
|View full text |Cite
|
Sign up to set email alerts
|

Implications of SNP weighting on single‐step genomic predictions for different reference population sizes

Abstract: We investigated the importance of SNP weighting in populations with 2,000 to 25,000 genotyped animals. Populations were simulated with two effective sizes (20 or 100) and three numbers of QTL (10, 50 or 500). Pedigree information was available for six generations; phenotypes were recorded for the four middle generations. Animals from the last three generations were genotyped for 45,000 SNP. Single-step genomic BLUP (ssGBLUP) and weighted ssGBLUP (WssGBLUP) were used to estimate genomic EBV using a genomic rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 29 publications
(56 reference statements)
7
51
0
Order By: Relevance
“…We expected that WssGBLUP would perform better for the scenarios SIM2 through SIM5, and especially for SIM4 and SIM5. Lourenco et al (2017) reported that for less polygenic traits (such as the simulated scenarios mentioned above), the accuracy might be higher when using WssGBLUP instead of ssGBLUP. WssGBLUP is advantageous for traits with a reduced number of causative genes because its assumption is similar to the genetic architecture of those traits: a finite number of markers affecting the trait.…”
Section: Ssgblup Vs Wssgblupmentioning
confidence: 99%
See 1 more Smart Citation
“…We expected that WssGBLUP would perform better for the scenarios SIM2 through SIM5, and especially for SIM4 and SIM5. Lourenco et al (2017) reported that for less polygenic traits (such as the simulated scenarios mentioned above), the accuracy might be higher when using WssGBLUP instead of ssGBLUP. WssGBLUP is advantageous for traits with a reduced number of causative genes because its assumption is similar to the genetic architecture of those traits: a finite number of markers affecting the trait.…”
Section: Ssgblup Vs Wssgblupmentioning
confidence: 99%
“…The WssGBLUP has been successfully applied to several genomic prediction studies (Zhang et al, 2016;Lourenco et al, 2017;Guarini et al, 2019). However, to our best knowledge, there are no reports evaluating the prediction ability of WssGBLUP in crossbred animals, especially in F1 populations.…”
Section: Introductionmentioning
confidence: 99%
“…Different formulas can be used to calculate SNP variance, but all of them are approximations. Several authors have reported decrease in GEBV accuracy and increase in bias over iterations [ 59 , 60 ] when variance is calculated based on squared SNP effects, especially for more polygenic traits. This is because SNP variance would reach extreme values over iterations.…”
Section: Software Methods and Algorithmsmentioning
confidence: 99%
“…Considering SNP variances when constructing G in ssGBLUP seems to improve the accuracy of predicting GEBV for data sets with small number of genotyped animals, but marginal or no improvement was observed for large genotyped populations (i.e., >10 k genotyped animals) [ 60 ], even for less polygenic traits. If the data allows to accurately estimate SNP effects, there is no advantage in selecting SNPs and tagging chromosome segments differently.…”
Section: Software Methods and Algorithmsmentioning
confidence: 99%
“…Alternatively, a number of studies proposed to weight the SNPs according to their effect or their variance to build the GRM in order to increase GBLUP prediction accuracy [10][11][12]. Different strategies have been proposed, relying on iterative schemes using SNP effects estimated from the GBLUP model [13][14][15][16] or on the posterior effects or variances obtained from some Bayesian methods [11,12,17]. It is also possible to directly estimate the variance associated with a single SNP or a subset of SNPs by fitting a specific GRM in a REML analysis (e.g., [18,19]).…”
Section: Introductionmentioning
confidence: 99%